Strategi Pengembangan Desa Wisata Berbasis Budaya Desa Bantiran, Kecamatan Pupuan,Kabupaten Tabanan, Provinsi Bali - I Komang Amerta Sedana; Ni Putu Indah Rahmawati; I Putu Gede Parma (Universitas Pendidikan Ganesha, 2022)
This study aimed to determine the strategy of developing a tourism village based on cultural tourism in Bantiran Village. This research uses descriptive qualitative research, by using the interview method, observation and documentation to collect data. The resource persons were taken from the Bendesa Adat of Bantiran Village. The results showed that Bantiran Village has a lot of tourism potential that can be developed by looking at its unique and religious culture. For this reason, cultural tourism in Bantiran Village can be developed by inviting the community to participate in the tourism village development strategy through Culture in Bantiran Village, disseminating to the community, especially those who work in the world of tourism to promote and provide knowledge on how to promote and develop tourist villages. In addition to this, village officials will support providing creative, innovative ideas to the community, preparing facilities such as home stay. It is hoped that this research can be useful for Bantiran Village in developing a village culture-based tourism village.